VALUE ADDED TAX AND GROSS DOMESTIC PRODUCT IN NIGERIA (Journal of Global Accounting, 2024)
This study assessed the effect of value added tax on gross domestic product in Nigeria for a period of eighteen years spanning from 2005 to 2022.  Based on the objectives of the study, four hypotheses were formulated. Ex-Post facto research design was adopted. The time series data were obtained from Federal Inland Revenue Services, Central Bank of Nigeria, National Bureau of Statistics and the World Bank Publications. As a preliminary step in testing, the study employed the Augmented Dickey Fully Unit root test to confirm the order of integration of the time series variables. The study employed inferential statistics using Ordinary Least Square (OLS) regression analysis, Pair-wise Granger Causality test, Johansen Co-integration test, and Error Correction Model. Specifically, the study found that value added tax has a positive and significant effect on gross domestic product (GDP) in Nigeria at 5% level of significance (β1 = 3785.152; P-value = 0.0335). It was recommended that government should diversify the economy for more development in order to increase the overall tax revenue base.
Keywords: Economic Development; Gross Domestic Product; Tax Rate; Value Added Tax